(3cJGH GdehGYXs - (3CHh YHO Gddg GdMSjf Hf eMeO GdNjGWjs ((3jhfS GdTQfLi GdgQeRi s)
(3ChdgG (B:s
(3HGH ai efGbH GdSjO CHGHcQ GdUOjb QVi Gddg Yfg bGd Gddg JYGdi (B:" (3hGddjd EPG jZTi Edi BNQgG bGd Cgd GdJaSjQ fRdJ gPg GdShQ ai Mb CHj HcQ QVi Gddg Yfg s
(3BNQgG (B:s
(3hGMTQ eY Wg GdHTjQ hBdg acd CeQ eY ef CMH ajMTQ eOG GdRgQ eG gH GdfSje Ydi GdQHG hSHMJ GdCWjGQ Ke JPGcQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(2016) s
Keywords: (3GdeLGejYs